Combination of searches for singly and doubly charged Higgs bosons produced via vector-boson fusion in proton–proton collisions at s=13 TeV with the ATLAS detector - Aad, G.; Åkesson, T.P.A. ; 0000-0003-4141-5408; Astrand, K.S.V.; Doglioni, C.; Ekman, P.A.; Hedberg, V.; Herde, H. ; 0000-0001-8926-6734; Konya, B.; Lytken, E. ; 0000-0002-8141-3995; Poettgen, R. ; 0000-0002-3304-0987; Smirnova, O. ; 0000-0003-2517-531X; Wallin, E.J.; et al. (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
A combination of searches for singly and doubly charged Higgs bosons, H± and H±±, produced via vector-boson fusion is performed using 140 fb−1 of proton–proton collisions at a centre-of-mass energy of 13 TeV, collected with the ATLAS detector during Run 2 of the Large Hadron Collider. Searches targeting decays to massive vector bosons in leptonic final states (electrons or muons) are considered. New constraints are reported on the production cross-section times branching fraction for charged Higgs boson masses between 200 GeV and 3000 GeV. The results are interpreted in the context of the Georgi-Machacek model for which the most stringent constraints to date are set for the masses considered in the combination. © 2024 CERN for the benefit of the ATLAS Collaboration